Battery management systems and inductive balancing - Bossche, Alex van den; Moghaddam, Ali Farzan (IET energy engineering series ;, 2021)
This book addresses practical approaches to managing batteries to ensure their reliability and longevity. Batteries are key to the energy transition, for both stationary and mobile applications, but their inner workings must be understood in order to ensure effective management.